In the service of public health–education in music therapy - Paulander, Ann-Sofie (Socialmedicinsk tidskrift, 2022)
Education in music pedagogy with a specialization in music therapy at bachelor’s level is conducted in Sweden at the Royal College of Music in Stockholm (KMH) were also a master’s program in the subject is under revision. KMH’s vision and mission includes contributing to the benefit of society through education in music therapy that can provide health care and medicine with music therapy expertise. Music therapy is an artistic form of therapy that has obtained scientific evidence in several areas. An education in music therapy at KMH is based on encounters between art and science where musical profession as well as academic knowledge and research are emphasized.